2021
DOI: 10.25259/sni_690_2021
|View full text |Cite
|
Sign up to set email alerts
|

Will the high acceptance rate of coronavirus disease 2019 vaccine in Morocco accelerate the recovery of neurosurgical practice?

Abstract: Background: In developing countries, where there is a chronic shortage of neurosurgeons and medical infrastructures, the pandemic has taken a heavy toll on neurosurgical activities. In the absence of a curative treatment, reaching herd immunity through mass vaccination campaigns is the best hope we have of ending this pandemic. Therefore, the purpose of our study was first to assess the effect of coronavirus disease 2019 (COVID-19) outbreak on neurosurgical services of a Moroccan tertiary hospital. Secondaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…vaccination campaign allowed them to recommence operations for brain tumours. (37) Another centre reported that glioblastoma cases were more aggressive than the previous year, with simple diagnostic biopsy often being management of choice. (29) Some centres described altered treatment pathways, for example, opting for either RT alone or in combination with surgery, (27) or cancelling operations and offering purely supportive care when benefit from active treatment was considered limited.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…vaccination campaign allowed them to recommence operations for brain tumours. (37) Another centre reported that glioblastoma cases were more aggressive than the previous year, with simple diagnostic biopsy often being management of choice. (29) Some centres described altered treatment pathways, for example, opting for either RT alone or in combination with surgery, (27) or cancelling operations and offering purely supportive care when benefit from active treatment was considered limited.…”
Section: Methods and Resultsmentioning
confidence: 99%
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified